A reassessment of the blood–brain barrier transport of large neutral amino acids during acute systemic inflammation in humans. (9th August 2017) - Dahl, Rasmus H.; Berg, Ronan M. G.; Taudorf, Sarah; Bailey, Damian M.; Lundby, Carsten; Larsen, Fin S.; Møller, Kirsten
Summary: We reassessed data from a previous study on the transcerebral net exchange of large neutral amino acids (LNAAs) using a novel mathematical model of blood–brain barrier (BBB) transport. The study included twelve healthy volunteers who received a 4‐h intravenous lipopolysaccharide (LPS) infusion (total dose: 0·3 ng/kg), a human experimental model of the systemic inflammatory response during the early stages of sepsis. Cerebral blood flow and arterial‐to‐jugular venous LNAA concentrations were measured prior to and after LPS, and the BBB transport and brain extracellular concentrations of LNAAs were calculated. The arterial concentration and unidirectional cerebral influx of phenylalanine increased after LPS. The BBB transport of tyrosine was unaffected, while its concentration in the brain extracellular fluid increased. These findings suggest that LPS infusion leads to an increased cerebral uptake of phenylalanine, which is then metabolized to tyrosine. This may reflect a neuroprotective mechanism that 'detoxifies' excess intracerebral phenylalanine in the clinical setting of sepsis.